High quality draft genome sequence of Flavobacterium rivuli type strain WB 3.3-2T (DSM 21788T), a valuable source of polysaccharide decomposing enzymes. Issue 1 (December 2015) - Hahnke, Richard; Stackebrandt, Erko; Meier-Kolthoff, Jan; Tindall, Brian; Huang, Sixing; Rohde, Manfred; Lapidus, Alla; Han, James; Trong, Stephan; Haynes, Matthew; Reddy, T.B.K.; Huntemann, Marcel; et al.
Abstract Flavobacterium rivuli Ali et al. 2009 emend. Dong et al. 2013 is one of about 100 species in the genusFlavobacterium (familyFlavobacteriacae, phylumBacteroidetes ) with a validly published name, and has been isolated from the spring of a hard water rivulet in Northern Germany. Including all type strains of the genusMyroides andFlavobacterium into the 16S rRNA gene sequence phylogeny revealed a clustering of members of the genusMyroides as a monophyletic group within the genusFlavobacterium . Furthermore, F. rivuli WB 3.3-2T and its next relatives seem more closely related to the genusMyroides than to the type species of the genusFlavobacterium, F. aquatile . The 4, 489, 248 bp long genome with its 3, 391 protein-coding and 65 RNA genes is part of theG enomic E ncyclopedia of B acteria and A rchaea project. The genome ofF. rivuli has almost as many genes encoding carbohydrate active enzymes (151 CAZymes) as genes encoding peptidases (177). Peptidases comprised mostly metallo (M) and serine (S) peptidases. Among CAZymes, 30 glycoside hydrolase families, 10 glycosyl transferase families, 7 carbohydrate binding module families and 7 carbohydrate esterase families were identified. Furthermore, we found four polysaccharide utilization loci (PUL) and one large CAZy rich gene cluster that might enable strain WB 3.3-2T to decompose plant and algae derived polysaccharides. Based on these results we proposeF. rivuli as an interesting candidate for further physiological studies and the role ofBacteroidetes in the decomposition of complex polymers in the environment.